Ekonomi kreatif digital: Peluang umkm di tahun 2025 - Rizkyan, Afis (Maliki Interdisciplinary Journal, 2025)
The advancement of digital technology has driven significant transformations in the economic sector, particularly in the creative economy. By 2025, digitalization presents strategic opportunities for Micro, Small, and Medium Enterprises (MSMEs) to grow faster, reach broader markets, and enhance their competitiveness in the era of globalization. This study aims to analyze the potentials and challenges faced by MSMEs in leveraging the digital creative economy ecosystem, as well as to formulate adaptive strategies to maximize these opportunities. A descriptive qualitative approach was employed, utilizing literature studies and interviews with MSMEs actors across various creative sectors. The findings indicate that digitalization enables access to e-commerce platforms, social media, and digital payment systems, all of which contribute to increased productivity and innovation. Nevertheless, low digital literacy, limited infrastructure, and funding constraints remain the main challenges. Therefore, synergy between the government, the private sector, and educational institutions is key to building an inclusive and sustainable digital ecosystem for MSMEs.